Crack growth propagation using standard FEM. (October 2016) - Formica, Giovanni; Milicchio, Franco
Highlights: We start from the formulation of Destuynder et al. (1981) and Formica et al. (2007). We focus on quasi-static crack growth as a sequence of linear equilibrium states. The formulation results from a domain transformation of the initial cracked body. Our target is to show how standard FEM yields results comparable to others. We compare our approach with enhanced numerical methods and real experiments. Abstract: This paper is part of research lines providing numerical methods for structural capability related to an evolving crack length in two-dimensional linear-elastic fracture mechanics of isotropic materials. We propose a numerical approach which efficiently simplifies more sophisticated approaches and yet, yield accurate results. Widely employed in academia, they are hardly used commercially unless ad hoc libraries are implemented. The proposed strategy improves early works where crack growth can be treated as a shape perturbation of the domain with existing cracks. The numerical results prove the accuracy of our strategy in comparison with both numerical and experimental outcomes present in literature.